'Disputed territories' in northern Iraq: The frontiering of in-between spaces. Issue 3 (26th May 2020) - Meier, Daniel
ABSTRACT: In Iraq, the disputed territories emerged as a key issue between the central government in Baghdad and Erbil, the capital of the Kurdistan Regional Government, since its recognition as an autonomous entity of the post-Baathist Iraq. Despite a resolution procedure drafted in an article of the new Constitution, approved by the Parliament in 2005, the disputed territories, understood as in-between spaces, knew a process of fragmentation due to a lack of political will to solve the issue and raising tension between Kurds, Arabs, and minorities living there. This paper intends to read this process with the concept of frontiering that links territory with power and violence while relying on a post-structuralist perspective to bridge territory and identity. Three places or cities like Kirkuk, Sinjar and Tuz Khurmatu will illustrate the power struggle and explore the variables of the frontiering process occurring in regions on the edge of Erbil–Baghdad influence while involving both local and regional geopolitical interests.